Developmental Expression and Glucocorticoid Control of the Leptin Receptor in Fetal Ovine Lung - De Blasio, Miles J.; Boije, Maria; Vaughan, Owen R.; Bernstein, Brett S.; Davies, Katie L.; Plein, Alice; Kempster, Sarah L.; Smith, Gordon C. S.; Charnock-Jones, D. Stephen; Blache, Dominique; Wooding, F. B. Peter; Giussani, Dino A.; et al. (PLOS ONE, 2015)
The effects of endogenous and synthetic glucocorticoids on fetal lung maturation are well-established, although the role of leptin in lung development before birth is unclear. This study examined mRNA and protein levels of the signalling long-form leptin receptor (Ob-Rb) in fetal ovine lungs towards term, and after experimental manipulation of glucocorticoid levels in utero by fetal cortisol infusion or maternal dexamethasone treatment. In fetal ovine lungs, Ob-Rb protein was localised to bronchiolar epithelium, bronchial cartilage, vascular endothelium, alveolar macrophages and type II pneumocytes. Pulmonary Ob-Rb mRNA abundance increased between 100 (0.69 fractional gestational age) and 144 days (0.99) of gestation, and by 2–4-fold in response to fetal cortisol infusion and maternal dexamethasone treatment. In contrast, pulmonary Ob-Rb protein levels decreased near term and were halved by glucocorticoid treatment, without any significant change in phosphorylated signal transducer and activator of transcription-3 (pSTAT3) at Ser727, total STAT3 or the pulmonary pSTAT3:STAT3 ratio. Leptin mRNA was undetectable in fetal ovine lungs at the gestational ages studied. These findings demonstrate differential control of pulmonary Ob-Rb transcript abundance and protein translation, and/or post-translational processing, by glucocorticoids in utero. Localisation of Ob-Rb in the fetal ovine lungs, including alveolar type II pneumocytes, suggests a role for leptin signalling in the control of lung growth and maturation before birth.